Semi-hydroponic cultivation of fertigated curly lettuce with calcium nitrate-enriched saline solutions - Pessoa, Victor G.; de Góis, Helena M. M. N.; de de Oliveira, Francisco A.; de Oliveira, Mychelle K. T.; Cordeiro, Carla J. X.; de Oliveira, Carlos E. A.; Costa, Mário J. V.; da Marques, Isabelly C. S. [UNESP] (FapUNIFESP (SciELO), 2023)
Lettuce is a leafy vegetable sensitive to salinity, and under saline stress conditions it presents nutritional imbalance, mainly in calcium absorption. Thus, the objective was to evaluate the effect of enriching the nutrient solution with calcium nitrate in solutions prepared with saline water in the lettuce crop. A completely randomized design was used, with five treatments and four replicates. The treatments were represented by five nutrient solutions [S1 - standard nutrient solution (SNP); S2 - SNP + NaCl (3.5 dS m-1); S3 - S2 + Ca (NO3)2 (50% = 6.86 mmol L-1); S4 - S2 + Ca(NO3)2 (100% = 9.15 mmol L-1); S5 - S2 + Ca(NO3)2 (150% = 11.43 mmol L-1)] in lettuce from the curly group, cv. Elba. After preparing the nutrient solutions, the solutions had the following electrical conductivities: 1.8 (S1); 4.8 (S2); 5.4 (S3); 6.0 (S4); 6.6 (S5) dS m-1. Variables of growth, nutrition and postharvest quality of lettuce were evaluated. With the exception of stem diameter, number of total leaves, plant pH and vitamin C content, the other variables were affected by the extra addition of Ca(NO3)2 in the nutrient solutions. The lettuce cv Elba grown in coconut fiber is tolerant to the salinity of 4.8 dS m-1 (S2). In conditions where the use of saline water with 3.5 dS m-1 for the preparation of the nutrient solution is unavoidable, the use of extra doses of Ca(NO3)2 in the lettuce crop is not recommended.
Cultivo semi-hidropônico de alface crespa fertirrigada com soluções salinas enriquecidas com nitrato de cálcio
Keywords: Hydroponics; Lactuca sativa L; Leafy vegetables; Salinity